Identification of in vitro and in vivo phosphorylation sites in the catalytic subunit of the DNA-dependent protein kinase. - Douglas, Pauline (2002)
The DNA-dependent protein kinase (DNA-PK) is required for the repair of DNA double-strand breaks (DSBs), such as those caused by ionizing radiation and other DNA-damaging agents. DNA-PK is composed of a large catalytic subunit (DNA-PKcs) and a heterodimer of Ku70 and Ku80 that assemble on the ends of double-stranded DNA to form an active serine/threonine protein kinase complex. Despite in vitro and in vivo evidence to support an essential role for the protein kinase activity of DNA-PK in the repair of DNA DSBs, the physiological targets of DNA-PK have remained elusive. We have previously shown that DNA-PK undergoes autophosphorylation in vitro, and that autophosphorylation correlates with loss of protein kinase activity and dissociation of the DNA-PK complex. Also, treatment of cells with the protein phosphatase inhibitor, okadaic acid, enhances DNA-PKcs phosphorylation and reduces DNA-PK activity in vivo. Here, using solid-phase protein sequencing, MS and phosphospecific antibodies, we have identified seven in vitro autophosphorylation sites in DNA-PKcs. Six of these sites (Thr2609, Ser2612, Thr2620, Ser2624, Thr2638 and Thr2647) are clustered in a region of 38 amino acids in the central region of the protein. Five of these sites (Thr2609, Ser2612, Thr2638, Thr2647 and Ser3205) are conserved between six vertebrate species. Moreover, we show that DNA-PKcs is phosphorylated in vivo at Thr2609, Ser2612, Thr2638 and Thr2647 in okadaic acid-treated human cells. We propose that phosphorylation of these sites may play an important role in DNA-PK function.